Los cuentos infantiles para mejorar la convivencia en niños de 4 a 5 años de la escuela de educación básica Luis Antonio Erique Ortega de la ciudad de Loja, periodo académico 2018-2019. - Velez Quizhpe, Gloria Stefania (2020)
The research entitled CHILDREN'S STORIES TO IMPROVE COEXISTENCE IN CHILDREN AGED 4 TO 5 FROM THE LUIS ANTONIO ERIQUE ORTEGA SCHOOL OF BASIC EDUCATION IN LOJA, ACADEMIC PERIOD 2018-2019; The general objective is to determine the importance of children's stories to improve coexistence in children between 4 and 5 years of age at the Luis Antonio Erique Ortega School of Basic Education; the review of literature addressed issues related to children's stories and coexistence; the methods were used in the research process: scientific, descriptive, inductive, deductive, descriptive statistics; the techniques and instruments applied were an interview, a survey and the Goldstein's Social Skills perception questionnaire; with a non-probabilistic sample; once the pre-test was applied, the results show that 43,94% develop sometimes; 40,30% develop often; 10,92% develop very rarely and 4,59% always develop the related social skills which does not guarantee good coexistence: In order to contribute to the improvement of coexistence, the proposal was designed and applied: let's live together, which was satisfactorily executed by means of an activity guide; once the post-test was carried out, it was noted that 52,51% often develop, 36,68% always develop and 10,80% sometimes develop these skills, and it was concluded that children's stories constitute an important strategy to improve coexistence in children.